2017
DOI: 10.1016/j.joep.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in research on preferences and personality traits: Measurement, stability, and inference

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Additionally, studies based on behavioral economic theory [3,5,6] have explained that one's decisions comprise both rational and irrational decisions, where irrational decisions are influenced by psychological factors. This is in line with Golsteyn and Schildberg-Hörisch's [7] opinion that "economic preferences and personality traits are related concepts in the sense that both are characteristics of the individual that have been shown to predict individual decisionmaking and life outcomes across a wide variety of domains." Based on the theoretical linkage above, it can be interpreted that personality traits influence a person's preference to add another child or not.…”
Section: Introductionsupporting
confidence: 85%
“…Additionally, studies based on behavioral economic theory [3,5,6] have explained that one's decisions comprise both rational and irrational decisions, where irrational decisions are influenced by psychological factors. This is in line with Golsteyn and Schildberg-Hörisch's [7] opinion that "economic preferences and personality traits are related concepts in the sense that both are characteristics of the individual that have been shown to predict individual decisionmaking and life outcomes across a wide variety of domains." Based on the theoretical linkage above, it can be interpreted that personality traits influence a person's preference to add another child or not.…”
Section: Introductionsupporting
confidence: 85%
“…In a meta-analysis conducted using longitudinal studies, Roberts et al (2006b) also showed statistically significant mean-level changes in Big Five personality traits in middle (40-60) and old (> 60) age. Personality changes can result from environmental changes in social roles or cultural milieu (Helson et al 2002a;Scollon and Diener 2006) or from life and work experiences (e.g., Roberts et al 2003;Roberts et al 2006a;Mroczek and Spiro 2003;Elkins et al 2017;Anger et al 2017;Golsteyn and Schildberg-Hörisch 2017).…”
Section: Description and Time Variability Of The Big Five Personalitymentioning
confidence: 99%
“…One solution is to fully accept the fact that such decisions arise partly from self-reflective activities that are more intense and frequent at critical life stages: adolescence, leaving the family nest, entering the job market, forming a family, 13 "To fall suddenly sick implies having to reinvent everything, to grasp again one's own life, to reassess thoroughly the order of one's relationships, one's work, one's own pleasures", Zaoui (2010, p. 79). Some economic research has examined the stability of risk, time, and social preferences (see Golsteyn and Schildberg-Horisch 2017). We are not aware of studies that would have specifically examined the impact of the onset of a chronic illness on preferences.…”
Section: Individual Identity and Preferencesmentioning
confidence: 99%